Activation and regulation of endogenous retroviral genes in the human pituitary gland and related endocrine tumours - Buslei, R.; Strissel, Pamela; Henke, Christine; Schey, Regina; Lang, Nadine; Ruebner, M.; Stolt, Claus; Fabry, Ben; Buchfelder, Michael; Strick, Reiner (Neuropathology and Applied Neurobiology, 2015)
Adenohypophysis (AH) hormone-producing cells represent the origin of diverse groups of pituitary adenomas (PA). Deregulation of hypothalamic hormone receptors, growth factors and cAMP signalling have been implicated in the aetiology of PA. Endogenous retroviruses (ERVs) are derived from past exogenous retroviral infections and represent more than 8% of the human genome. Some ERV genes encode open reading frames and produce functional proteins, for example, the ERVW-1 envelope gene Syncytin-1, essential for placentogenesis, but also deregulated in human tumours. Data concerning ERV expression in the AH and related endocrine tumours are missing.Syncytin-1 protein was analysed in normal AH (n = 15) and compared with five PA subtypes (n = 117) by immunohistochemistry. Absolute gene expression of 20 ERV functional envelope genes and ERVW-5 gag was measured. PA tissues were examined for Syncytin-1 and the cAMP signalling marker phospho-CREB-Ser133 using immunohistochemistry. Isolated primary human PA cells were treated with different hormones. Murine embryonic and adult pituitary gland ERV expressions were compared with human AH.Syncytin-1 protein colocalized with corticotropic cells of AH. In contrast, all PA demonstrated significant Syncytin-1 protein overexpression, supporting deregulation. All other ERV genes showed significant up-regulations in different PA subtypes. Phospho-CREB-Ser133 and Syncytin-1 colocalized in PA cells. Cultivated primary PA cells with ACTH or CRH induced their respective receptors and ERV genes. Syncytin-A/-B, murine orthologues to human Syncytin-1/-2, localized to embryonic and adult pituitary glands demonstrating functional mammalian conservation.Deregulated ERV genes may contribute to PA development via cAMP signalling.
EVALuna2:4955

Development and degeneration of dorsal root ganglia in the absence of the HMG-domain transcription factor Sox10 - Wegner, Michael; Stolt, Claus; et al. (Mechanisms of Development, 2001)
The HMG-domain transcription factor Sox10 is essential for the development of various neural crest derived lineages including glia and neurons of the peripheral nervous system (PNS). Within the PNS the most striking defect is the complete absence of glial differentiation whereas neurogenesis seemed initially normal. A degeneration of motoneurons and sensory neurons occurred later in development. The mechanism that leads to the dramatic effects on the neural crest derived cell lineages in the dorsal root ganglia (DRG), however, has not been examined up to now. Here, we provide a detailed analysis of proliferation and apoptosis in the DRG during the time of their generation and lineage segregation (between E 9.5 and E 11.5). We show that both increased apoptosis as well as decreased proliferation of neural crest cells contribute to the observed hypomorphism. © 2001 Elsevier Science Ireland Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2001.med.IB.LPCIPDBI.develo

Erythropoietin production by PDGFR-?(+) cells - Gerl, Katharina; Nolan, Karen A.; Karger, Christian; Fuchs, Michaela; Wenger, Roland H.; Stolt, Claus; Willam, Carsten; Kurtz, Armin; Kurt, Birguel (Pflügers Archiv: European Journal of Physiology, 2016)
PDGFR-?-expressing cells of the kidneys are considered as a relevant site of erythropoietin (EPO) production. The origin of these cells, their contribution to renal EPO production, and if PDGFR-?-positive cells in other organs are also capable to express EPO are less clear. We addressed these questions in mice, in which hypoxia-inducible transcription factors were stabilized in PDGFR-?(+) cells by inducible deletion of the von Hippel-Lindau (Vhl) protein. Vhl deletion led to a 600-fold increase of plasma EPO concentration, 170-fold increase of renal EPO messenger RNA (mRNA) levels, and an increase of hematocrit values up to 70 %. Intrarenal localization of EPO-expressing cells coincided with the zonal heterogeneity and distribution of cells expressing PDGFR-?. Amongst a variety of extrarenal organs only adrenal glands showed significant EPO mRNA expression after Vhl deletion in PDGFR-?(+) cells. EPO mRNA, plasma EPO, and hematocrit fell to subnormal values if HIF-2?, but not HIF-1?, was deleted either alone or in combination with Vhl in PDGFR-?(+) cells. Treatment of mice with a prolyl-hydroxylase inhibitor caused an increase of EPO mRNA abundance and plasma EPO concentrations in wild-type mice and in mice lacking HIF-1? in PDGFR-?(+) cells but exerted no effect in mice lacking HIF-2? in PDGFR-?(+) cells. These findings suggest that PDGFR-?(+) cells are the only relevant site of EPO expression in the kidney and that HIF-2 is the essential transcription factor triggering EPO expression therein. Moreover, our findings suggest that PDGFR-?(+) cells elaborating EPO might arise from the metanephric mesenchyme, rather than from the neural crest.
EVALuna2:3861

From stem cells to neurons and glia: a soxist's view of neural development. - Wegner, Michael; Stolt, Claus (Trends in Neurosciences, 2005)
During nervous system development, neural stem cells give rise to many different types of neurons and glia over an extended period. Little is known about the intrinsic factors that regulate stem-cell maintenance, decide whether neurons or glia are generated, or control terminal differentiation. Transcription factors of the Sox family provide important clues about the control of these events. In the central nervous system (CNS), Sox1, Sox2 and Sox3 are required for stem-cell maintenance, and their effects are counteracted by Sox21. Sox9, by contrast, alters the potential of stem cells from neurogenic to gliogenic, whereas Sox10 is essential for terminal oligodendrocyte differentiation. In the peripheral nervous system (PNS) the same Sox proteins have different functions, uncovering important developmental differences between the CNS and PNS. © 2005 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2005.med.IB.LPCIPDBI.fromst

Glial but not neuronal development in the cochleo-vestibular ganglion requires Sox10. - Stolt, Claus; Wegner, Michael; et al. (Journal of Neurochemistry, 2010)
The cochleo-vestibular ganglion contains neural crest-derived glial cells and sensory neurons that are derived from the neurogenic otic placode. Little is known about the molecular mechanisms that regulate the tightly orchestrated development of this structure. Here, we report that Sox10, a high-mobility group DNA-binding domain transcription factor that is required for the proper development of neural crest cell derivatives, is specifically expressed in post-migratory neural crest cells in the cochleo-vestibular ganglion. Using Sox10-deficient mice, we demonstrate that this transcription factor is essential for the survival, but not the generation, of the post-migratory neural crest cells within the inner ear. In the absence of these neural crest-derived cells, we have investigated the survival of the otocyst-derived auditory neurons. Surprisingly, auditory neuron differentiation, sensory target innervation and survival are conserved despite the absence of glial cells. Moreover, brain-derived neurotrophic factor expression is increased in the hair cells of Sox10-deficient mice, a compensatory mechanism that may prevent spiral ganglion neuronal cell death. Taken together, these data suggest that in the absence of neural crest-derived glial cells, an increase trophic support from hair cells promotes the survival of spiral ganglion neurons in Sox10 mutant mice. © 2010 International Society for Neurochemistry.
UnivIS-Import:2015-03-09:Pub.2010.med.IB.LPCIPDBI.glialb
Keywords: auditory neurons; development; glial cells; inner ear; neural crest cells; Sox genes

Identification of Sox8 as a modifier gene in a mouse model of Hirschsprung disease reveals underlying molecular defect. - Wegner, Michael; Stolt, Claus; et al. (Developmental Biology, 2005)
Mice carrying heterozygous mutations in the Sox10 gene display aganglionosis of the colon and represent a model for human Hirschsprung disease. Here, we show that the closely related Sox8 functions as a modifier gene for Sox10-dependent enteric nervous system defects as it increases both penetrance and severity of the defect in Sox10 heterozygous mice despite having no detectable influence on enteric nervous system development on its own. Sox8 exhibits an expression pattern very similar to Sox10 with occurrence in vagal and enteric neural crest cells and later confinement to enteric glia. Loss of Sox8 alleles in Sox10 heterozygous mice impaired colonization of the gut by enteric neural crest cells already at early times. Whereas proliferation, apoptosis, and neuronal differentiation were normal for enteric neural crest cells in the gut of mutant mice, apoptosis was dramatically increased in vagal neural crest cells outside the gut. The defects in enteric nervous system development of mice with Sox10 and Sox8 mutations are therefore likely caused by a reduction of the pool of undifferentiated vagal neural crest cells. Our study suggests that Sox8 and Sox10 are jointly required for the maintenance of these vagal neural crest stem cells. © 2004 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2005.med.IB.LPCIPDBI.identi
Keywords: Enteric nervous system; High-mobility-group; Hirschsprung disease; Megacolon; Sox10; Sry

Impact of transcription factor Sox8 on oligodendrocyte specification in the mouse embryonic spinal cord. - Sock, Elisabeth; Wegner, Michael; Stolt, Claus; et al. (Developmental Biology, 2005)
The myelin-forming oligodendrocytes of the mouse embryonic spinal cord express the three group E Sox proteins Sox8, Sox9, and Sox10. They require Sox9 for their specification from neuroepithelial cells of the ventricular zone and Sox10 for their terminal differentiation and myelination. Here, we show that during oligodendrocyte development, Sox8 is expressed after Sox9, but before Sox10. Loss of Sox8 did not impair oligodendrocyte specification by itself, but enhanced the Sox9-dependent defect. Oligodendrocyte progenitors were still generated in the Sox9-deficient spinal cord, albeit at 20-fold lower rates than in the wildtype. Combined loss of Sox8 and Sox9, in contrast, led to a near complete loss of oligodendrocytes. Other cell types such as ventricular zone cells and radial glia remained unaffected in their numbers as well as their rates of proliferation and apoptosis. Oligodendrocyte development thus relies on the differential contribution of all three group E Sox proteins at various phases. © 2005 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2005.med.IB.LPCIPDBI.impact
Keywords: Glia; High-mobility-group; Knockout; Oligodendrogenesis; Redundancy; Sox10; Sox9; Sry

Mutual antagonism between Sox10 and NFIA regulates diversification of glial lineages and glioma subtypes - Glasgow, Stacey M.; Zhu, Wenyi; Stolt, Claus; Huang, Teng-Wei; Chen, Fuyi; Loturco, Joseph J.; Neul, Jeffrey L.; Wegner, Michael; Mohila, Carrie; Deneen, Benjamin (Nature Neuroscience, 2014)
Lineage progression and diversification is regulated by the coordinated action of unique sets of transcription factors. Oligodendrocytes (OL) and astrocytes (AS) comprise the glial sub-lineages in the CNS, and the manner in which their associated regulatory factors orchestrate lineage diversification during development and disease remains an open question. Sox10 and NFIA are key transcriptional regulators of gliogenesis associated with OL and AS. We found that NFIA inhibited Sox10 induction of OL differentiation through direct association and antagonism of its function. Conversely, we found that Sox10 antagonized NFIA function and suppressed AS differentiation in mouse and chick systems. Using this developmental paradigm as a model for glioma, we found that this relationship similarly regulated the generation of glioma subtypes. Our results describe the antagonistic relationship between Sox10 and NFIA that regulates the balance of OL and AS fate during development and demonstrate for the first time, to the best of our knowledge, that the transcriptional processes governing glial sub-lineage diversification oversee the generation of glioma subtypes.
EVALuna2:4965

Neural crest origin of perivascular mesenchyme in the adult thymus. - Stolt, Claus; Wegner, Michael; et al. (Journal of Immunology, 2008)
The endodermal epithelial thymus anlage develops in tight association with neural crest (NC)-derived mesenchyme. This epithelial-NC interaction is crucial for thymus development, but it is not known how NC supports thymus development or whether NC cells or their progeny make any significant contribution to the adult thymus. By nude mouse blastocyst complementation and by cell surface phenotype, we could previously separate thymus stroma into Foxn1-dependent epithelial cells and a Foxn1-independent mesenchymal cell population. These mesenchymal cells expressed vascular endothelial growth factor-A, and contributed to thymus vascularization. These data suggested a physical or functional association with thymic blood vessels, but the origin, location in the thymus, and function of these stromal cells remained unknown. Using a transgenic mouse expressing Cre recombinase in premigratory NC (Sox10-Cre), we have now fate-mapped the majority of these adult mesenchymal cells to a NC origin. NC-derived cells represent tightly vessel-associated pericytes that are sandwiched between endothelium and epithelium along the entire thymus vasculature. The ontogenetic, phenotypic, and positional definition of this distinct perivascular mesenchymal compartment provides a cellular basis for the role of NC in thymus development and possibly maintenance, and might be useful to address properties of the endothelial-epithelial barrier in the adult thymus. Copyright © 2008 by The American Association of Immunologists, Inc.
UnivIS-Import:2015-03-09:Pub.2008.med.IB.LPCIPDBI.neural

Neural crest origin of retinal and choroidal pericytes - Trost, Andrea; Schroedl, Falk; Lange, Simona; Rivera, Francisco J.; Tempfer, Herbert; Korntner, Stefanie; Stolt, Claus; Wegner, Michael; Bogner, Barbara; Kaser-Eichberger, Alexandra; Krefft, Karolina; Runge, Christian; et al. (Investigative Ophthalmology & Visual Science, 2013)
The origin of pericytes (PCs) has been controversially discussed and at least three different sources of PCs are proposed: a neural crest, mesodermal, or bone marrow origin. In the present study we investigated a potential neural crest origin of ocular PCs in a transgenic Rosa26-YFP-Sox10-Cre neural crest-specific reporter mouse model at different developmental stages.The Rosa26-YFP-Sox10-Cre mouse model expresses the yellow fluorescent protein (YFP) reporter in cells with an active Sox10 promoter and was here used for cell fate studies of Sox10-positive neural crest derived progeny cells. Detection of the YFP signal in combination with double and triple immunohistochemistry of chondroitin sulfate proteoglycan (NG2), platelet derived growth factor receptor ? (PDGFR?), ? smooth muscle actin (?SMA), oligodendrocyte transcription factor 2 (Olig2), and lectin was performed and analyzed by confocal microscopy.Sox10-YFP-positive cells and profiles were detected in the inner nuclear layer, the ganglionic cell layer, and the axons of the nerve fiber layer in postnatal retinas. An additional population has been identified in the retina, optic nerve, and choroid that displays strong perivascular localization. These cells were colocalized with the PC-specific markers NG2 and PDGFR? in embryonic (E14.5) as well as postnatal (P4, P12, 6-week-old) vasculature. Beside PCs, vascular smooth muscle cells (vSMCs) were also labeled by the Sox10-YFP reporter protein in all ocular tissues investigated.Since YFP-positive PCs and vSMCs are colocalized with NG2 and PDGFR?, we propose that capillary PCs and vSMCs in the retina and the optic nerve, both parts of the central nervous system, as well as in the choroid, a tissue of mesodermal origin, derive from the neural crest.
EVALuna2:4935

Olfactory ensheathing cells abutting the embryonic olfactory bulb express Frzb, whose deletion disrupts olfactory axon targeting - Rich, Constance A.; Perera, Surangi N.; Andratschke, Jacqueline; Stolt, Claus; Buehler, Dennis P.; Southard-Smith, E. Michelle; Wegner, Michael; Britsch, Stefan; Baker, Clare V. H. (Glia, 2018)
We and others previously showed that in mouse embryos lacking the transcription factor Sox10, olfactory ensheathing cell (OEC) differentiation is disrupted, resulting in defective olfactory axon targeting and fewer gonadotropin-releasing hormone (GnRH) neurons entering the embryonic forebrain. The underlying mechanisms are unclear. Here, we report that OECs in the olfactory nerve layer express Frzb-encoding a secreted Wnt inhibitor with roles in axon targeting and basement membrane breakdown-from embryonic day (E)12.5, when GnRH neurons first enter the forebrain, until E16.5, the latest stage examined. The highest levels of Frzb expression are seen in OECs in the inner olfactory nerve layer, abutting the embryonic olfactory bulb. We find that Sox10 is required for Frzb expression in OECs, suggesting that loss of Frzb could explain the olfactory axon targeting and/or GnRH neuron migration defects seen in Sox10-null mice. At E16.5, Frzb-null embryos show significant reductions in both the volume of the olfactory nerve layer expressing the maturation marker Omp and the number of Omp-positive olfactory receptor neurons in the olfactory epithelium. As Omp upregulation correlates with synapse formation, this suggests that Frzb deletion indeed disrupts olfactory axon targeting. In contrast, GnRH neuron entry into the forebrain is not significantly affected. Hence, loss of Frzb may contribute to the olfactory axon targeting phenotype, but not the GnRH neuron phenotype, of Sox10-null mice. Overall, our results suggest that Frzb secreted from OECs in the olfactory nerve layer is important for olfactory axon targeting.
EVALuna2:35737

Olfactory ensheathing glia are required for embryonic olfactory axon targeting and the migration of gonadotropin-releasing hormone neurons - Barraud, Perrine; St John, James A.; Stolt, Claus; Wegner, Michael; Baker, Clare V. H. (Biology Open, 2013)
Kallmann's syndrome is caused by the failure of olfactory axons and gonadotropin-releasing hormone (GnRH) neurons to enter the embryonic forebrain, resulting in anosmia and sterility. Sox10 mutations have been associated with Kallmann's syndrome phenotypes, but their effect on olfactory system development is unknown. We recently showed that Sox10 is expressed by neural crest-derived olfactory ensheathing cells (OECs). Here, we demonstrate that in homozygous Sox10(lacZ/lacZ) mouse embryos, OEC differentiation is disrupted; olfactory axons accumulate in the ventromedial olfactory nerve layer and fewer olfactory receptor neurons express the maturation marker OMP (most likely owing to the failure of axonal targeting). Furthermore, GnRH neurons clump together in the periphery and a smaller proportion enters the forebrain. Our data suggest that human Sox10 mutations cause Kallmann's syndrome by disrupting the differentiation of OECs, which promote embryonic olfactory axon targeting and hence olfactory receptor neuron maturation, and GnRH neuron migration to the forebrain.
EVALuna2:4943

Oligodendroglial-specific transcriptional factor SOX10 is ubiquitously expressed in human gliomas. - Wegner, Michael; Stolt, Claus; et al. (Journal of Neuro-Oncology, 2006)
UnivIS-Import:2015-03-09:Pub.2006.med.IB.LPCIPDBI.oligod

Onset of Spinal Cord Astrocyte Precursor Emigration from the Ventricular Zone Involves the Zeb1 Transcription Factor - Ohayon, David; Garces, Alain; Joly, Willy; Soukkarieh, Chadi; Takagi, Tsuyoshi; Sabourin, Jean-Charles; Agius, Eric; Darling, Douglas S.; Barbara, Pascal De Santa; Higashi, Yujiro; Stolt, Claus; Hugnot, Jean-Philippe; et al. (Cell Reports, 2016)
During spinal cord development, astrocyte precursors arise from neuroepithelial progenitors, delaminate from the ventricular zone, and migrate toward their final locations where they differentiate. Although the mechanisms underlying their early specification and late differentiation are being deciphered, less is known about the temporal control of their migration. Here, we show that the epithelial-mesenchymal transition regulator Zeb1 is expressed in glial precursors and report that loss of Zeb1 function specifically delays the onset of astrocyte precursor delamination from the ventricular zone, correlating with transient deregulation of the adhesion protein Cadherin-1. Consequently, astrocyte precursor invasion into the Zeb1(-/-) mutant white matter is delayed, and induction of their differentiation is postponed. These findings illustrate how fine regulation of adhesive properties influences the onset of neural precursor migration and further support the notion that duration of exposure of migrating astrocyte precursors to environmental cues and/or their correct positioning influence the timing of their differentiation.
EVALuna2:4996

Radial glia phagocytose axonal debris from degenerating overextending axons in the developing olfactory bulb - Amaya, Daniel A.; Wegner, Michael; Stolt, Claus; Chehrehasa, Fatemeh; Ekberg, Jenny A. K.; St John, James A. (Journal of Comparative Neurology, 2015)
Axon targeting during the development of the olfactory system is not always accurate, and numerous axons overextend past the target layer into the deeper layers of the olfactory bulb. To date, the fate of the mis-targeted axons has not been determined. We hypothesized that following overextension, the axons degenerate, and cells within the deeper layers of the olfactory bulb phagocytose the axonal debris. We utilized a line of transgenic mice that expresses ZsGreen fluorescent protein in primary olfactory axons. We found that overextending axons closely followed the filaments of radial glia present in the olfactory bulb during embryonic development. Following overextension into deeper layers of the olfactory bulb, axons degenerated and radial glia responded by phagocytosing the resulting debris. We used in vitro analysis to confirm that the radial glia had phagocytosed debris from olfactory axons. We also investigated whether the fate of overextending axons was altered when the development of the olfactory bulb was perturbed. In mice that lacked Sox10, a transcription factor essential for normal olfactory bulb development, we observed a disruption to the morphology and positioning of radial glia and an accumulation of olfactory axon debris within the bulb. Our results demonstrate that during early development of the olfactory system, radial glia play an important role in removing overextended axons from the deeper layers of the olfactory bulb.
EVALuna2:4966

Regulation of murine placentogenesis by the retroviral genes Syncytin-A, Syncytin-B and Peg10 - Henke, Christine; Ruebner, Matthias; Faschingbauer, Florian; Stolt, Claus; Schäfer, Natascha; Lang, Nadine; Beckmann, Matthias; Strissel, Pamela; Strick, Reiner (Differentiation, 2013)
The murine placenta has a trichorial structure with two multinucleated syncytiotrophoblast (SCT) layers representing a barrier between the maternal and fetal blood system. Genes of endogenous retroviruses and retrotransposon-derived paternally expressed genes (Peg), remnants of past infections and integrations in the genome, have essential functions in placentogenesis. Previous studies showed that the envelope genes Syncytin-A and Syncytin-B were essential for cell-cell fusion of the SCT. The goal of this study was to analyze the temporal localization and expression of nine genes throughout placental development from embryonic day (E)8.5 to E18.5 using in situ-hybridization and absolute RNA-quantification. These included a comparison of previously characterized genes from the labyrinth Syncytin-A, Syncytin-B, Gcm1, the junctional zone PL-1, PL-2, Plf, Tpbpa with two further characterized genes Peg10 and Tpbpb. Syncytin-A and Syncytin-B RNA localized to SCT-I and SCT-II, respectively. Peg10 RNA localized to all extraembryonic tissues, specifically to the parietal and sinusoidal TGC of the labyrinth layer, which is in contact with SCT-I and the maternal blood. All three retroviral/retrotransposon-derived genes showed the highest expression at E16.5, but Peg10 with 188,917.1 molecules/ng cDNA was 208-fold and 106.8-fold higher expressed than Syncytin-A and Syncytin-B, respectively. Tpbpb localized to the junctional zone and showed the highest expression at E16.5 along with PL-2, Plf, Tpbpa, but not PL-1, which decreased in expression at E10.5. To investigate a role of Syncytin-A, Syncytin-B and Peg10 in cell-cell fusion, we established a cell culture system with fractionated primary trophoblasts from murine placentae. Culturing trophoblasts for up to 72h partly resembled trophoblast development in vivo according to the nine marker genes. Knockdown of Syncytin-A demonstrated a functional regulation of cell-cell fusion, where knockdown of Peg10 showed no involvement in cell fusion. Due to the expression of Peg10 in TGCs, we propose an essential functional role in the fetal-maternal blood system.
EVALuna2:4934

Replacement of related POU transcription factors leads to severe defects in mouse forebrain development. - Sock, Elisabeth; Reiprich, Simone; Müller, Jana; Stolt, Claus; Wegner, Michael; et al. (Developmental Biology, 2009)
Related transcription factors of the POU protein family show extensive overlap of expression in vivo and exhibit very similar biochemical properties in vitro. To study functional equivalence of class III POU proteins in vivo, we exchanged the Oct-6 gene by Brn-1 in the mouse. Brn-1 can fully replace Oct-6 in Schwann cells and rescue peripheral nervous system development in these mice. The same mice, however, exhibit severe defects in forebrain development arguing that Oct-6 and Brn-1 are not functionally equivalent in the central nervous system. The cause of the observed forebrain phenotype is complex, but anteriorly expanded Wnt1 expression contributes. Oct-6 normally represses Wnt1 expression in the early diencephalon and replacement by Brn-1 as a weaker inhibitor is no longer sufficient to maintain the necessary level of repression in the mouse mutant. The extent of functional equivalence between related transcription factors is thus strongly dependent on the analyzed tissue. © 2009 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.med.IB.LPCIPDBI.replac
Keywords: Brain malformation; Brn-1; Functional equivalence; Homeodomain; Oct-6; Redundancy; Transcription factor; Wnt signalling

Replacement of the Sox10 transcription factor by Sox8 reveals incomplete functional equivalence. - Wegner, Michael; Stolt, Claus; et al. (Development, 2006)
Sox8 and Sox10 are two closely related transcription factors of the Sox protein family with overlapping expression patterns during development. They are believed to perform very similar functions because several developmental processes, including enteric nervous system development and oligodendrocyte differentiation, are regulated by both Sox proteins. To analyze the extent of functional equivalence between the two Sox proteins, we employed targeted mutagenesis to replace Sox10 with Sox8 in the mouse. In mice that expressed Sox8 instead of Sox10, Sox10 deficiency was phenotypically rescued to different extents in affected tissues. Whereas development of glial cells and neurons in the sensory and sympathetic parts of the peripheral nervous system was almost normal when Sox10 was replaced by Sox8, melanocyte development was as defective as in Sox10-deficient mice. The ability of Sox8 to rescue the defects in enteric nervous system development and oligodendrocyte differentiation of Sox10-deficient mice was limited. We conclude that the extent of functional equivalence depends on the tissue and that, despite their relatedness, Sox8 and Sox10 have more unique functions than previously appreciated.
UnivIS-Import:2015-03-09:Pub.2006.med.IB.LPCIPDBI.replac
Keywords: Glia; High-mobility-group; Neural crest; Oligodendrocyte; Redundancy; Sry

Restricted expression of mouse GCMa/Gcm1 in kidney and thymus - Hashemolhosseini, Said; Stolt, Claus; Wegner, Michael; et al. (Mechanisms of Development, 2002)
Mouse Glial Cells Missing a (mGCMa) belongs to a small family of transcription factors named after the prototypical GCM from Drosophila. mGCMa was expected to regulate gliogenesis, but instead found to be primarily expressed during development in trophoblasts of chorion and labyrinth. Its deletion causes abnormal placental labyrinth formation and results in embryonic lethality. Here we identify kidney and thymus as sites of mGCMa expression. In thymus, mGCMa is restricted to few small clusters of cells, in kidney to the S3 segment of proximal tubules. mGCMa expression is primarily postnatal, arguing for a role in organ function rather than organ development. © 2002 Elsevier Science Ireland Ltd. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2002.med.IB.LPCIPDBI.restri
Keywords: GCM; Kidney; Thymus; Proximal tubule; S3 segment

Schwann cells and their transcriptional network: Evolution of key regulators of peripheral myelination - Stolt, Claus; Wegner, Michael (Brain Research, 2016)
As derivatives of the neural crest, Schwann cells represent a vertebrate invention. Their development and differentiation is under control of a newly constructed, vertebrate-specific regulatory network that contains Sox10, Oct6 and Krox20 as cornerstones and central regulators of peripheral myelination. In this review, we discuss the function and relationship of these transcription factors among each other and in the context of their regulatory network, and present ideas of how neofunctionalization may have helped to recruit them to their novel task in Schwann cells. This article is part of a Special Issue entitled SI: Myelin Evolution.
EVALuna2:4985

Selective expression of sense and antisense transcripts of the sushi-ichi-related retrotransposon - derived family during mouse placentogenesis - Henke, Christine; Strissel, Pamela; Schubert, Maria-Theresa; Mitchell, Megan; Stolt, Claus; Faschingbauer, Florian; Beckmann, Matthias; Strick, Reiner (Retrovirology, 2015)
LTR-retrotransposons became functional neogenes through evolution by acquiring promoter sequences, regulatory elements and sequence modification. Mammalian retrotransposon transcripts (Mart1-9), also called sushi-ichi-related retrotransposon-homolog (SIRH) genes, are a class of Ty3/gypsy LTR-retroelements showing moderate homology to the sushi-ichi LTR-retrotransposon in pufferfish. Rtl1/Mart1 and Peg10/Mart2 expression in mouse placenta and demonstration of their functional roles during placental development exemplifies their importance in cellular processes. In this study, we analyzed all eleven mouse Mart genes from the blastocyst stage and throughout placentogenesis in order to gain information about their expression and regulation.Quantitative PCR, in situ hybridization (ISH) and immunoblotting showed various expression patterns of the 11 mouse Mart genes through different placental stages. Zcchc5/Mart3, Zcchc16/ Mart4 and Rgag1/Mart9 expression was undetectable. Rtl1/Mart1, Peg10/Mart2, Rgag4/Mart5 - Cxx1a,b,c/Mart8b,c,a gene expression was very low at the blastocyst stage. Later placental stages showed an increase of expression for Rtl1/Mart1, Rgag4/Mart5 - Cxx1a,b,c/Mart8b,c,a, the latter up to 1,489 molecules/ng cDNA at E9.5. From our recently published findings Peg10/Mart2 was the most highly expressed Mart gene. ISH demonstrated sense and antisense transcript co-localization of Rgag4/Mart5 to Cxx1a,b,c/Mart8b,c,a in trophoblast subtypes at the junctional zone, with an accumulation of antisense transcripts in the nuclei. To validate these results, we developed a TAG-aided sense/antisense transcript detection (TASA-TD) method, which verified sense and antisense transcripts for Rtl1/Mart1, Rgag4/Mart5 - Cxx1a,b,c/Mart8b,c,a. Except for Rtl1/Mart1 and Cxx1a,b/Mart8b,c all other Mart genes showed a reduced amount of antisense transcripts. Northern blot and 5' and 3' RACE confirmed both sense and antisense transcripts for Ldoc1/Mart7 and Cxx1a,b,c/Mart8b,c,a. Immunoblotting demonstrated a single protein throughout all placental stages for Ldoc1/Mart7, but for Cxx1a,b,c/Mart8b,c,a a switch occurred from a 57 kDa protein at E10.5 and E14.5 to a 25 kDa protein at E16.5 and E18.5.RNA and protein detection of mouse Mart genes support neo-functionalization of retrotransposons in mammalian genomes. Undetectable expression of Zcchc5/Mart3, Zcchc16/Mart4 and Rgag1/Mart9 indicate no role during mouse placentogenesis. Rgag4/Mart5 to Cxx1a,b,c/Mart8b,c,a gene expression support a role for differentiation from the ectoplacental cone. Mart antisense transcripts and protein alterations predict unique and complex molecular regulation in a time directed manner throughout mouse placentogenesis.
EVALuna2:4979

Sox13 functionally complements the related Sox5 and Sox6 as important developmental modulators in mouse spinal cord oligodendrocytes - Baroti, Tina; Schillinger, Anja; Wegner, Michael; Stolt, Claus (Journal of Neurochemistry, 2016)
The role of transcription factor Sox13, which together with Sox5 and Sox6 belongs to the SoxD family, is only poorly characterized in central nervous system development. Therefore, we analysed whether Sox13 expression and function overlaps with or differs from that of its close relatives Sox5 and Sox6. In the developing mouse spinal cord, we found Sox13 predominantly expressed in neuroepithelial precursors, oligodendroglial and astroglial cells. The substantially overlapping expression with Sox5 and Sox6 in oligodendroglial cells prompted us to study potential roles during specification, lineage progression and differentiation of oligodendrocytes. In contrast to Sox5 and Sox6, Sox13 expression continues after differentiation and even increases in myelinating oligodendrocytes. Sox13 deletion did not interfere with oligodendroglial development, which was normal in Sox13-deficient mice. However, the premature differentiation of oligodendrocyte precursors triggered by loss of Sox6 was slightly more prominent in Sox6/Sox13 double-deficient mice. Sox13 can bind to the same sites in myelin gene promoters as Sox5 and Sox6 in vitro. Reporter gene assays furthermore reveal a similar antagonizing effect on Sox10-dependent transactivation of myelin gene promoters as previously shown for Sox5 and Sox6. This argues that Sox13 is functionally redundant with the other SoxD proteins and complements Sox5 and Sox6 in their role as important modulators of oligodendrocyte development. The transcription factor Sox13 is co-expressed with the related Sox5 and Sox6 in cells of the oligodendroglial lineage. By itself, it has little impact on oligodendrocyte development but supports Sox5 and Sox6 during the process as a functionally redundant transcription factor.
EVALuna2:4987

Sox5 controls dorsal progenitor and interneuron specification in the spinal cord - Quiroga, Alejandra C.; Stolt, Claus; Diez Del Corral, Ruth; Dimitrov, Spas; Perez-Alcala, Siro; Sock, Elisabeth; Barbas, Julio A.; Wegner, Michael; Morales, Aixa V. (Developmental Neurobiology, 2015)
The basic organization of somatosensory circuits in the spinal cord is already setup during the initial patterning of the dorsal neural tube. Extrinsic signals, such as Wnt and TGF-? pathways, activate combinatorial codes of transcription factors that are responsible for generating a pattern of discrete domains of dorsal progenitors (dp). These progenitors will give rise to distinct dorsal interneurons (dI). The Wnt/ ?catenin signaling pathway controls specification of dp/dI1-3 progenitors and interneurons. According to the current model in the field, Wnt/?catenin activity seems to act in a graded fashion in the spinal cord, as different relative levels determine the identity of adjacent progenitors. However, it is not clear how this activity gradient is controlled and how the identities of dI1-3 are differentially regulated by Wnt signalling. We have determined that two SoxD transcription factors, Sox5 and Sox6, are expressed in restricted domains of dorsal progenitors in the neural tube. Using gain- and loss-of function approaches in chicken embryos, we have established that Sox5 controls cell fate specification of dp2 and dp3 progenitors and, as a result, controls the correct number of the corresponding dorsal interneurons (dI2 and dI3). Furthermore, Sox5 exerts its function by restricting dorsally Wnt signaling activity via direct transcriptional induction of the negative Wnt pathway regulator Axin2. By that way, Sox5 acts as a Wnt pathway modulator that contributes to sharpen the dorsal gradient of Wnt/?catenin activity to control the distinction of two functionally distinct types of interneurons, dI2 and dI3 involved in the somatosensory relay.
EVALuna2:4962

Sox9 and Sox10 influence survival and migration of oligodendrocyte precursors in the spinal cord by regulating PDGF receptor alpha expression. - Stolt, Claus; Wegner, Michael; et al. (Development, 2008)
Specification of the myelin-forming oligodendrocytes of the central nervous system requires the Sox9 transcription factor, whereas terminal differentiation depends on the closely related Sox10. Between specification and terminal differentiation, Sox9 and Sox1O are co-expressed in oligodendrocyte precursors and are believed to exert additional functions. To identify such functions, we have deleted Sox9 specifically in already specified oligodendrocyte precursors of the spinal cord. In the absence of Sox9, oligodendrocyte precursors developed normally and started terminal differentiation on schedule. However, when Sox10 was additionally deleted, oligodendrocyte precursors exhibited an altered migration pattern and were present in reduced numbers because of increased apoptosis rates. Remaining precursors continued to express many characteristic oligodendroglial markers. Aberrant expression of astrocytic and neuronal markers was not observed. Strikingly, we failed to detect PDGF receptor a expression in the mutant oligodendrocyte precursors, arguing that PDGF receptor α is under transcriptional control of Sox9 and Sox10. Altered PDGF receptor α expression is furthermore sufficient to explain the observed phenotype, as PDGF is both an important survival factor and migratory cue for oligodendrocyte precursors. We thus conclude that Sox9 and Sox10 are required in a functionally redundant manner in oligodendrocyte precursors for PDGF-dependent survival and migration.
UnivIS-Import:2015-03-09:Pub.2008.med.IB.LPCIPDBI.sox9an
Keywords: Glia; High-mobility group; PDGF; Redundancy; SoxE; Sry; Transgenic mice

SoxD proteins influence multiple stages of oligodendrocyte development and modulate SoxE protein function. - Sock, Elisabeth; Wegner, Michael; Stolt, Claus; et al. (Developmental Cell, 2006)
The myelin-forming oligodendrocytes are an excellent model to study transcriptional regulation of specification events, lineage progression, and terminal differentiation in the central nervous system. Here, we show that the group D Sox transcription factors Sox5 and Sox6 jointly and cell-autonomously regulate several stages of oligodendrocyte development in the mouse spinal cord. They repress specification and terminal differentiation and influence migration patterns. As a consequence, oligodendrocyte precursors and terminally differentiating oligodendrocytes appear precociously in spinal cords deficient for both Sox proteins. Sox5 and Sox6 have opposite functions than the group E Sox proteins Sox9 and Sox10, which promote oligodendrocyte specification and terminal differentiation. Both genetic as well as molecular evidence suggests that Sox5 and Sox6 directly interfere with the function of group E Sox proteins. Our studies reveal a complex regulatory network between different groups of Sox proteins that is essential for proper progression of oligodendrocyte development. © 2006 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2006.med.IB.LPCIPDBI.soxdpr
Keywords: DEVBIO

SoxE function in vertebrate nervous system development. - Stolt, Claus; Wegner, Michael (International Journal of Biochemistry & Cell Biology, 2010)
Sox8, Sox9, and Sox10 as transcription factors of subgroup E of the Sox protein family are essential for many aspects of nervous system development. These SoxE proteins are already required for the initial neural crest induction, but also guarantee survival and maintenance of pluripotency in migrating neural crest stem cells. SoxE proteins are furthermore key regulators of glial specification in both the peripheral and the central nervous systems. At later stages of development, Sox10 plays crucial roles in Schwann cells and oligodendrocytes for terminal differentiation and myelin formation. In both glial cell types, Sox10 controls directly the expression of genes encoding the major myelin proteins. SoxE proteins are well-integrated components of regulatory networks and as such modulated in their activity by cooperating or antagonistic transcription factors such as SoxD or various bHLH proteins. The multiple functions in peripheral and central nervous system development also link SoxE proteins to various human diseases and identify these proteins as promising targets of future therapeutic approaches. © 2009 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2010.med.IB.LPCIPDBI.soxefu
Keywords: Astrocyte; Differentiation; Oligodendrocyte; Schwann cell; Specification

SoxE proteins are differentially required in mouse adrenal gland development. - Reiprich, Simone; Stolt, Claus; Wegner, Michael; et al. (Molecular Biology of the Cell, 2008)
Sry-box (Sox)8, Sox9, and Sox10 are all strongly expressed in the neural crest. Here, we studied the influence of these closely related transcription factors on the developing adrenal medulla as one prominent neural crest derivative. Whereas Sox9 was not expressed, both Sox8 and Sox10 occurred widely in neural crest cells migrating to the adrenal gland and in the gland itself, and they were down-regulated in cells expressing catecholaminergic traits. Sox10-deficient mice lacked an adrenal medulla. The adrenal anlage was never colonized by neural crest cells, which failed to specify properly at the dorsal aorta and died apoptotically during migration. Furthermore, mutant neural crest cells did not express Sox8. Strong adrenal phenotypes were also observed when the Sox10 dimerization domain was inactivated or when a transactivation domain in the central portion was deleted. Sox8 in contrast had only minimal influence on adrenal gland development. Phenotypic consequences became only visible in Sox8-deficient mice upon additional deletion of one Sox10 allele. Replacement of Sox10 by Sox8, however, led to significant rescue of the adrenal medulla, indicating that functional differences between the two related Sox proteins contribute less to the different adrenal phenotypes of the null mutants than dependence of Sox8 expression on Sox10. © 2008 by The American Society for Cell Biology.
UnivIS-Import:2015-03-09:Pub.2008.med.IB.LPCIPDBI.soxepr

Terminal differentiation of myelin-forming oligodendrocytes depends on the transcription factor Sox10 - Wegner, Michael; Stolt, Claus; et al. (Genes & Development, 2002)
Sox10 is a high-obility-group transcriptional regulator in early neural crest. Without Sox10, no glia develop throughout the peripheral nervous system. Here we show that Sox10 is restricted in the central nervous system to myelin-forming oligodendroglia. In Sox10-deficient mice progenitors develop, but terminal differentiation is disrupted. No myelin was generated upon transplantation of Sox10-deficient neural stem cells into wild-type hosts showing the permanent, cell-autonomous nature of the defect. Sox10 directly regulates myelin gene expression in oligodendrocytes, but does not control erbB3 expression as in peripheral glia. Sox10 thus functions in peripheral and central glia at different stages and through different mechanisms.
UnivIS-Import:2015-03-09:Pub.2002.med.IB.LPCIPDBI.termin
Keywords: Glial cells; HMG; MBP; Neuregulin; PLP; Sox

The Sox9 transcription factor determines glial fate choice in the developing spinal cord. - Sock, Elisabeth; Wegner, Michael; Stolt, Claus; et al. (Genes & Development, 2003)
The mechanism that causes neural stem cells in the central nervous system to switch from neurogenesis to gliogenesis is poorly understood. Here we analyzed spinal cord development of mice in which the transcription factor Sox9 was specifically ablated from neural stem cells by the CRE/loxP recombination system. These mice exhibit defects in the specification of oligodendrocytes and astrocytes, the two main types of glial cells in the central nervous system. Accompanying an early dramatic reduction in progenitors of the myelin-forming oligodendrocytes, there was a transient increase in motoneurons. Oligodendrocyte progenitor numbers recovered at later stages of development, probably owing to compensatory actions of the related Sox10 and Sox8, both of which overlap with Sox9 in the oligodendrocyte lineage. In agreement, compound loss of Sox9 and Sox10 led to a further decrease in oligodendrocyte progenitors. Astrocyte numbers were also severely reduced in the absence of Sox9 and did not recover at later stages of spinal cord development. Taking the common origin of motoneurons and oligodendrocytes as well as V2 interneurons and some astrocytes into account, stem cells apparently fail to switch from neurogenesis to gliogenesis in at least two domains of the ventricular zone, indicating that Sox9 is a major molecular component of the neuron-glia switch in the developing spinal cord.
UnivIS-Import:2015-03-09:Pub.2003.med.IB.LPCIPDBI.thesox
Keywords: Astrocyte; HMG-box; Neural stem cell; Oligodendrocyte; Sox10; Sry

The transcription factor Sox10 is an essential determinant of branching morphogenesis and involution in the mouse mammary gland - Mertelmeyer, Svenja; Weider, Matthias; Baroti, Tina; Reiprich, Simone; Fröb, Franziska; Stolt, Claus; Wagner, Kay Uwe; Wegner, Michael (Scientific Reports, 2020)
The high mobility group-domain containing transcription factor Sox10 is an essential regulator of developmental processes and homeostasis in the neural crest, several neural crest-derived lineages and myelinating glia. Recent studies have also implicated Sox10 as an important factor in mammary stem and precursor cells. Here we employ a series of mouse mutants with constitutive and conditional Sox10 deficiencies to show that Sox10 has multiple functions in the developing mammary gland. While there is no indication for a requirement of Sox10 in the specification of the mammary placode or descending mammary bud, it is essential for both the prenatal hormone-independent as well as the pubertal hormone-dependent branching of the mammary epithelium and for proper alveologenesis during pregnancy. It furthermore acts in a dosage-dependent manner. Sox10 also plays a role during the involution process at the end of the lactation period. Whereas its effect on epithelial branching and alveologenesis are likely causally related to its function in mammary stem and precursor cells, this is not the case for its function during involution where Sox10 seems to work at least in part through regulation of the miR-424(322)/503 cluster.
CRIS-Team Scopus Importer:2020-10-30

The transcription factor Sox5 modulates Sox10 function during melanocyte development. - Stolt, Claus; Hillgärtner, Simone; Wegner, Michael; et al. (Nucleic Acids Research, 2008)
The transcription factor Sox5 has previously been shown in chicken to be expressed in early neural crest cells and neural crest-derived peripheral glia. Here, we show in mouse that Sox5 expression also continues after neural crest specification in the melanocyte lineage. Despite its continued expression, Sox5 has little impact on melanocyte development on its own as generation of melanoblasts and melanocytes is unaltered in Sox5-deficient mice. Loss of Sox5, however, partially rescued the strongly reduced melanoblast generation and marker gene expression in Sox10 heterozygous mice arguing that Sox5 functions in the melanocyte lineage by modulating Sox10 activity. This modulatory activity involved Sox5 binding and recruitment of CtBP2 and HDAC1 to the regulatory regions of melanocytic Sox10 target genes and direct inhibition of Sox10-dependent promoter activation. Both binding site competition and recruitment of corepressors thus help Sox5 to modulate the activity of Sox10 in the melanocyte lineage.
UnivIS-Import:2015-03-09:Pub.2008.med.IB.LPCIPDBI.thetra

Transcription factors Sox5 and Sox6 exert direct and indirect influences on oligodendroglial migration in spinal cord and forebrain - Baroti, Tina; Zimmermann, Yvonne; Schillinger, Anja; Liu, Lina; Lommes, Petra; Wegner, Michael; Stolt, Claus (Glia, 2016)
Transcription factors of the SoxD protein family have previously been shown to prevent precocious specification and terminal differentiation of oligodendrocyte progenitor cells in the developing spinal cord. Using mice with specific deletion of the SoxD proteins Sox5 and Sox6 in the central nervous system, we now show that SoxD proteins additionally influence migration of oligodendrocyte progenitors in the spinal cord as well as in the forebrain. In mutant mice, emigration of oligodendrocyte progenitors from the ventricular zone and colonization of the mantle zone are significantly delayed probably because of reduced expression of Pdgf receptor alpha and decreased responsiveness toward Pdgf-A as a main migratory cue. In addition to this direct cell-autonomous effect on Pdgf receptor alpha expression, SoxD proteins furthermore promote oligodendroglial migration by keeping the cells in an undifferentiated state and preventing a premature loss of their migratory capacity. This indirect effect becomes particularly important during late embryonic and early postnatal phases of oligodendroglial development. Finally, we show that Sox5 and Sox6 cooperate with Sox9 and Sox10 to activate Pdgf receptor alpha expression and thereby maintain oligodendrocyte progenitors in the immature state. This contrasts with their behavior on myelin genes where they antagonize the function of SoxE proteins. It argues that SoxD proteins can function either as repressors or as co-activators of SoxE proteins thereby modulating their function in a stage-specific manner.
EVALuna2:4986

Transcription factors Sox8 and Sox10 perform non-equivalent roles during oligodendrocyte development despite functional redundancy. - Wegner, Michael; Stolt, Claus; et al. (Development, 2004)
Development of myelin-forming oligodendrocytes in the central nervous system is dependent on at least two members of the Sox family of high-mobility-group-containing transcription factors. Sox9 is involved in oligodendrocyte specification, whereas Sox10 is required for terminal differentiation. We show that oligodendrocytes in the spinal cord additionally express the highly related Sox8. In Sox8-deficient mice, oligodendrocyte development proceeded normally until birth. However, terminal differentiation of oligodendrocytes was transiently delayed at early postnatal times. Sox8-deficient mice thus exhibited a similar, but less severe phenotype than did Sox10-deficient mice. Terminal oligodendrocyte differentiation was dramatically delayed in Sox8-deficient mice with only a single functional Sox10 allele hinting at redundancy between both Sox proteins. This redundancy was also evident from the fact that Sox8 bound to naturally occurring Sox10 response elements, was able to form DNA-dependent heterodimers with Sox10 and activated Sox10-specific oligodendrocytic target genes in a manner similar to Sox10. However, Sox8 expression levels were significantly lower than those for Sox10. Resulting differences in protein amounts might be a main reason for the weaker impact of Sox8 on oligodendrocyte development and for unidirectional compensation of the Sox8 loss by Sox10.
UnivIS-Import:2015-03-09:Pub.2004.med.IB.LPCIPDBI.transc
Keywords: Gene dosage; High-mobility-group; Oligodendrocyte; Redundancy; Sox10; Sry